Maximization of Contractor Business Competencies Resulting from Project Team Competencies - Dr. Kittipos Kawesittisankhun; Dr. Jakrapong Pongpeng (My University, 2023)
Under the current circumstances of highly competitive business operations, contractors should allocate their resources to develop the project team competencies, then leading to the improvement of the contractors’ business competencies. A question is how the contractors’ limited resources should be allocated to develop the project team competencies and thus maximize the contractor's business competencies. A literature review shows that few research works have addressed this question, showing a knowledge gap that should be filled. Therefore, this research aimed to answer this question by developing a linear programming model that suggests optimal resource allocation to improve the project team competencies. A survey case study in the Thai construction industry was used to illustrate the model application. The results of the model application show that the optimal proportion of resource allocation to develop the project team competencies should be as follows: physical health (32.80%), communication (16.30%), knowledge (15.60%), decision-making (10.60%), relationship management (9.80%), systematic construction work (9.80%), and systematic management (5.20%). These results can be used as a suggestion for the contractors’ optimal resource allocation to develop their project team competencies and maximize contractor business competencies.
Keywords: Project team; Construction Project Management and Performance